Protective Effect of Broken Pine Pollen on Cadmium-poisoned Rats - Yan XING; Shuai SHAO; Xiaoxian HE; Shuhui SONG; Limei ZHANG (Shipin gongye ke-ji, 2025)
Objective: Investigating the protective effect of broken pine pollen on cadmium-poisoned rats. Methods: Fifty male SD rats were randomly divided into control, model, low, medium, and high-dose pine pollen groups. The models and pine pollen intervention groups were intraperitoneally injected with cadmium chloride (0.2 mg/kg body weight), and rats in the low, medium, and high dose groups of pine pollen were fed daily with 1, 2, and 3 g of broken pine pollen, respectively, for 28 d. Levels of cadmium and zinc in the blood, liver, kidneys, femur, testicles, feces, and urine of rats, as well as related physical and chemical indicators and gene expression levels, and histological changes were observed and detected. Results: Compared with the control, the testicular index of the model rats was significantly decreased (P<0.05), and the cadmium content in serum, femur, liver, kidneys, and testicles significantly increased (P<0.05). Severe histological changes were observed in the kidney and testicle in models, while the pine pollen treatments alleviated pathological damages to the kidney and testicle to varying degrees, with the high-dose group showed better improvement than the low and medium dose group. Compared with the model group, intervention with high-dose pine pollen significantly increased serum superoxide dismutase (SOD) levels, decreased lipid peroxidation (LPO) levels (P<0.05), up-regulated nuclear factor erythroid 2-related factor 2 (Nrf2), heme oxygenase 1 (HO-1) and B-cell lymphoma-2 (Bcl-2) gene expression and down-regulated Caspase-3 gene expression in testicles (P<0.05). Furthermore, the intervention promoted the excretion of cadmium in feces and urine, significantly reduced cadmium accumulation in rats, and increased zinc levels (P<0.05). Conclusion: Broken pine pollen can exert protective effects on cadmium-induced toxicity by activating the Nrf2/HO-1 pathway, enhancing the body's antioxidant capacity, and increasing zinc intake, promoting cadmium excretion.